Power system analysis - Saadat, Hadi. ([S.l.] : Mcgraw-Hill College, 1998)
Power System Analysis, is intended to provide complete coverage of power system analysis and design. It gives an introduction to fundamentals concepts and modern topics with applications to real-world problems. This is the first book in this area to full integrate MATLAB and SIMULINK throughout.